Draft Five Year Plan 1980-85 North Eastern Council - Planning Commission (Planning Commission, 1980)
While the second year of the Sixth Five Year Plan was under way, the Planning Commission felt that the objectives of the plan needed to be reviewed to reflect the shift in the priorities in the Government policies. Accordingly, taking note of the guidelines received from the Planning Commission the reformulation of the Sixth Five Year Plan 1980-85 was undertaken.
North Eastern Council